Efficacy and safety of praziquantel and dihydroartemisinin piperaquine combination for treatment and control of intestinal schistosomiasis: A randomized, non-inferiority clinical trial. - Rajabu Hussein Mnkugwe; Omary Minzi; Safari Kinung'hi; Appolinary Kamuhabwa; Eleni Aklillu (Public Library of Science (PLoS), 2020)
Background Despite the reported success in reducing morbidity, praziquantel alone is insufficient for the control and elimination of schistosomiasis, partly due to its poor efficacy against the juvenile worms. Artemisinin derivatives are effective against juvenile worms but are less effective against adult worms. We compared the safety and efficacy of praziquantel and Dihydroartemisinin-piperaquine combination against the standard praziquantel alone for treatment of intestinal schistosomiasis. Methods In this randomized, open-label, non-inferiority trial, 639 Schistosoma mansoni infected children were enrolled and randomized to receive either praziquantel alone or praziquantel plus Dihydroartemisinin-piperaquine combination. Two stool samples were collected on consecutive days at baseline, 3 and 8 weeks post-treatment and analyzed using thick smear Kato Katz method. Efficacy was assessed by cure and egg reduction rates at 3 and 8 weeks post-treatment. Adverse events were assessed within four hours of drugs intake. The primary outcome was cure rates at 8 weeks of post-treatment. Secondary outcomes were egg reduction rates at 8 weeks of post-treatment and treatment-associated adverse events. Results At 3 weeks of post-treatment, cure rates were 88.3% (263/298, 95% CI = 84.1%- 91.4%) and 81.2% (277/341, 95% CI = 76.7%- 85.0%) for the combination therapy and praziquantel alone, respectively (p < 0.01, odds ratio (OR) = 1.74, 95% CI of OR = 1.11 to 2.69). At 8 weeks, there was a significant drop in the cure rates in praziquantel alone group to 63.9% (218/341, 95% CI = 58.7%- 68.8%) compared to 81.9% (244/298, 95% CI = 77.1%- 85.8%) in the combination therapy group (p < 0.0001, OR = 2.55, 95%CI of OR = 1.75 to 3.69). Egg reduction rates at 8 weeks post-treatment were significantly higher in the combination therapy group 93.6% (95% CI = 90.8%- 96.4%) compared to 87.9% (95% CI = 84.4%- 91.4%) in the praziquantel only group (p = 0.01). On both Univariate and Multivariate regression analysis, type of treatment received was a significant predictor of cure at week 8 post-treatment. Overall, 30.8% (95% CI = 27.2%- 34.4%) of the study participants experienced mild and transient treatment-associated adverse events, post-treatment abdominal pain (27.1%) being the most common adverse event observed. There was no significant difference in the overall occurrence of adverse events between the two treatment groups. Conclusion Praziquantel and Dihydroartemisinin piperaquine combination therapy is safe, and more efficacious compared to praziquantel alone for the treatment of intestinal schistosomiasis. Further studies are needed to explore if the combination therapy can be considered as an option for mass drug administration to control and eventually eliminate schistosomiasis.